2018
DOI: 10.22146/ijc.21170
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calcination Temperature on the Synthesis of ZrO<sub>2</sub>-Pillared Saponite to Catalytic Activity in Menthol Esterification

Abstract: The influence of calcination temperature on the synthesis of zirconia-pillared saponite (PILS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Supports present a similar NH 3 desorption profile, but the calcined one presents a little bit more acidity than the fresh one. Some authors explain that this slight difference between the two supports is probably due to the presence of zirconium sites acting as Lewis acid sites besides the formation of H + as a Bronsted acid from the calcination processes 51 and/or due to the change of the ZrO 2 phase. 52 The acidity of the ZrO 2 is slightly changed when the fraction of the tetragonal phase is increased, 53 and this phase change occurs when the calcination temperature is maintained at 450 °C during different times.…”
Section: Methodsmentioning
confidence: 99%
“…Supports present a similar NH 3 desorption profile, but the calcined one presents a little bit more acidity than the fresh one. Some authors explain that this slight difference between the two supports is probably due to the presence of zirconium sites acting as Lewis acid sites besides the formation of H + as a Bronsted acid from the calcination processes 51 and/or due to the change of the ZrO 2 phase. 52 The acidity of the ZrO 2 is slightly changed when the fraction of the tetragonal phase is increased, 53 and this phase change occurs when the calcination temperature is maintained at 450 °C during different times.…”
Section: Methodsmentioning
confidence: 99%
“…In the few last decades, the raised of utilized from the photocatalysts and nanocatalysts was regarded as versatile materials such as produced of solar cells [1][2], decolorized and degradation of organic compounds [3][4][5][6][7][8] used as biosensor [9][10], synthesis some organic compounds in certain reactions [11], using as anticancer and antitumor [12][13], and using in SPF solar emulsions as sunscreen [14][15].…”
Section: ■ Introductionmentioning
confidence: 99%
“…The commercial zirconia was used as control. All samples indicate three diffraction peaks at 2θ value of about 28°, 31°, and 50° which can be indexed as (11-1), (111) and (122) reflection planes of monoclinic crystal phase of zirconia (JCPDS 37-1484), respectively [24]. Acid treatment on zirconia surprisingly exhibited higher crystallinity, as shown that the peaks intensity of the sulfated zirconia diffraction was increased, compared to the commercial zirconia.…”
Section: Resultsmentioning
confidence: 88%